2007
DOI: 10.1021/bi700340n
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Physiological Turnover of Native and Inactivated Cytochromes P450 3A in Cultured Rat Hepatocytes:  A Role for the Cytosolic AAA ATPase p97?

Abstract: Mammalian hepatic cytochromes P450 (P450s) are endoplasmic reticulum (ER)-anchored hemoproteins engaged in the metabolism of numerous xeno-and endobiotics. P450s exhibit widely ranging half-lives, utilizing both autophagic-lysosomal (ALD) and ubiquitin-dependent 26S proteasomal (UPD) degradation pathways. Although suicidally inactivated hepatic CYPs 3A and "native" CYP3A4 in S. cerevisiae are degraded via UPD, the turnover of native hepatic CYPs 3A in their physiological milieu has not been elucidated. Herein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
62
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(72 citation statements)
references
References 59 publications
(171 reference statements)
10
62
0
Order By: Relevance
“…Collectively, our findings above together with our previous reports (5)(6)(7)(8)(9)(10)(11)(12)(13)(14) led us to propose a mechanistic scheme for CYP3A ERAD/UPD (Fig. 6), wherein the P450 protein requires to be first phosphorylated by both PKA (or a PKA-like kinase) and PKC on a distinct set of residues, for its subsequent recognition by UbcH5a/CHIP/Hsp70 and UBC7/gp78 E2-E3 ubiquitination complexes, following which the ubiquitinated protein is extracted out of the ER by the p97/Ufd1/Npl4 AAA ATPase complex and delivered to the 26 S proteasome for degradation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Collectively, our findings above together with our previous reports (5)(6)(7)(8)(9)(10)(11)(12)(13)(14) led us to propose a mechanistic scheme for CYP3A ERAD/UPD (Fig. 6), wherein the P450 protein requires to be first phosphorylated by both PKA (or a PKA-like kinase) and PKC on a distinct set of residues, for its subsequent recognition by UbcH5a/CHIP/Hsp70 and UBC7/gp78 E2-E3 ubiquitination complexes, following which the ubiquitinated protein is extracted out of the ER by the p97/Ufd1/Npl4 AAA ATPase complex and delivered to the 26 S proteasome for degradation.…”
Section: Discussionsupporting
confidence: 89%
“…We have documented that CYP3A4, in common with its CYP3A orthologs, incurs ubiquitin (Ub)-dependent proteasomal degradation (UPD) in a classical ER-associated degradation (ERAD) process (2)(3)(4). Indeed, irrespective of any detectable structural lesion(s) in their cytosolic domain, CYPs 3A function as typical ERAD-C substrates (2)(3)(4)(5)(6)(7)(8). Accordingly, we have previously shown that both native and structurally/functionally inactivated CYPs 3A including CYP3A4 incur protein phosphorylation, followed by ubiquitination by UBC7/gp78 and UbcH5a/CHIP (C terminus of Hsc70-interacting protein) E2-E3 systems, p97-mediated ER-extraction, and subsequent 26 S proteasomal degradation (8 -14).…”
mentioning
confidence: 99%
“…Cells were treated with vehicle (ethanol or DMSO) and proteasomal inhibitor MG-262 (20 M), MG-132 (20 M), or epoxomycin (10 M), with or without DDEP (100 M) for 0 -6 h. Hepatocytes from another human donor were also similarly cultured and treated with rifampin. On the 5th day they were treated with a combination of lysosomal inhibitors 3-methyladenine (3MA; 5 mM) and NH 4 Cl (50 mM) for 20 h, along with a DMSO vehicle control (16). Total cell lysate protein (20 g) was assayed by Western immunoblotting for CYP2E1 content as described above.…”
Section: ␥-S-[mentioning
confidence: 99%
“…We and others have documented that in this ERAD-C process, CYPs 3A and CYP2E1 are first phosphorylated by protein kinases (PKA and PKC) (30, 34 -38), ubiquitinated by the cytosolic UbcH5a-CHIP-Hsc70-Hsp40 and UBC7-dependent ERintegral polytopic gp78 E2-E3-Ub-ligase complexes (29,30,(37)(38)(39)(40), extracted from the ER membrane by the Npl4-Ufd1-p97/VCP-AAA ATPase chaperone complex (12,41), and then delivered to the 26 S proteasome for degradation. Herein, we document that although each of these E2-E3 systems can function quite independently in vitro, when present concurrently as in vivo, their roles in CYP3A4 ubiquitination are complementary rather than redundant.…”
mentioning
confidence: 99%